Consumption of food away from home (FAFH) a study of selected Filipino families in Quezon City - Juani, Frances Joy S.; Bantang, Joanne R. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
The study described the experiences and practices of selected urban Filipino families on the rising trend of consuming food away from home (FAFH). It illuminated on the lived experiences of the family in terms of food consumption frequency, variety, nutrition, expenses, and meal time. It also shed light on the mealtime environment and value of FAFH as a practice. Phenomenological approach was used in this study to gain an in-depth analysis of the FAFH phenomenon. The study focused on urban Filipino families residing in Quezon City. Mothers who are the household food managers were purposively selected to be interviewed in this study. The researcher used an interview guide during the data gathering to have an organized flow and the better encapsulate the experiences of families through the mothers. The prevailing themes from the study are as follows: 1) families consume lesser nutritional quality of food when they eat out (FAFH) compared to when they eat at home (FAH); 2) eating out provides working mothers more time, relaxation, and convenience; 3) food- and service-related characteristics enhance the experience and encourage consumption of FAFH; 4) variety of experiences and practices of FAFH consumption relates to income; 5) family decisions and reasons of FAFH consumption change as children grow older; 6) families' food consumption experiences strengthens relationships as a results of eating out; and 7) family rules and traditions during mealtimes are carried out even when eating outside the home. In conclusions, the seven themes can be further summarized into two essential components which are pragmatic and enhancing. eating out has pragmatic components; families consume FAFH for practically. Eating out also has an enhancing component since FAFH become a means to strengthen family relationships. FAFH has positive and negative effects for the family, this study recommends that families should highlight the benefits of FAFH consumption such as strengthening relationships and decrease its negative impact such as consuming unhealthy meals.
Thesis (B.S. Home Economics)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Food preferences -- Philippines -- Quezon City; Food habits -- Philippines -- Quezon City; Food consumption -- Philippines -- Quezon City